Circulating microRNAs as novel minimally invasive biomarkers for breast cancer - Heneghan, Helen M; Miller, Nicola; Lowery, Aoife J; Sweeney, Karl J; Newell, John; Kerin, Michael J (Annals of surgery, 2010)
The development of clinically validated biomarkers for cancer has remained an insurmountable task despite other advances in the field of cancer molecular biology. Mi(cro)RNAs have many characteristics of an ideal biomarker most notably their inherent stability and resilience. Recent blood-based miRNA profiling studies, reporting their presence in serum and plasma, have generated the concept that circulating miRNAs hold much potential as novel noninvasive biomarkers for cancer and other disease processes. The objective of this study was to investigate the potential of circulating microRNAs as novel breast cancer biomarkers. Using a novel approach to extract miRNAs from the circulation followed by real-time quantitative polymerase chain reaction analysis, levels of a panel of 7 candidate miRNAs were quantified in tissue and blood specimens of 148 patients with breast cancer and 44 age-matched and disease free control individuals. We report that cancer-specific miRNAs were detected and significantly altered in the circulation of breast cancer patients, and that increased systemic miR-195 levels in breast cancer patients were reflected in breast tumors. Furthermore, we identified that circulating levels of miR-195 and let-7a decreased in cancer patients postoperatively, to levels comparable with control subjects, following curative tumor resection. Finally, we found that specific circulating miRNAs correlated with certain clinicopathological variables, namely nodal status and estrogen receptor status. These findings suggest that systemic miRNAs have potential use as novel breast cancer biomarkers and may prove useful in clinical management during the perioperative period.